Analgesia, anesthesia monitoring and perioperative care - Antunes, Luis (Henry Stewart Talks, 2016)
Importance of analgesia in laboratory animal sciences, Pain assessment, Perioperative pain treatment, Local and regional anesthesia or analgesia, Anesthesia monitoring, Post-anesthesia